Evaluation of Water Quality Parameters for Shatt Al-Basrah Canal in Basrah Authorities - Gatea, Mudhar H.; Dakhil, Ammar A.; Dawood, Ammar S. (Science Journal of University of Zakho, 2018)
A significant increase in freshwater demand has been reported recently due to several factors such as population growth, industrialization, rising living standards and global warming effects. As a direct result of that, numerous water crises have occurred around the world especially in downstream countries such as Iraq. Due to the previous reasons, water in terms of quality and quantity considered as a first priority by the Iraqi government. This study focuses on Basrah city, which is located in the south region. The purpose of this research is evaluating the physicochemical qualities of water from the Shatt Al-Basrah Canal to evaluate its suitability to be used for domestic or industrial uses. Data gathered from two sampling stations located on the canal to measure the physicochemical characteristics of the water such as pH, Ca, Mg, PO4, Cl, SO4, DO, NO3, TDS, and EC. With this specific purpose, water samples were collected from the study area, and the water quality has been evaluated. Water samples were collected during six months period during 2013 for assessment purposes. The results of the analysis were assessed according to international water standards for drinking water. From these results of this study, it is often asserted that there is a water pollution in the Shatt Al-Basrah canal and therefore immediate protective actions need to be utilized to minimize the pollution and improve water quality.